Zinc, un elemento químico muy versátil - Piedra Marín, Gilberto (Pontificia Universidad Católica del Perú, 2019)
Zinc is a shiny metal whose surface quickly darkens upon contact with air. The main industrial application of this metal is the galvanization of iron and steel parts. Peru is the second largest producer of zinc worldwide, and regionally, the Ancash region is the first producer of this metal.

El zinc es un metal brillante cuya superficie se oscurece rápidamente al contacto con el aire. La principal aplicación industrial de este metal es la galvanización de piezas de hierro y acero. Perú es segundo productor de zinc a nivel mundial, y a nivel regional, la región de Áncash es la primera productora de este metal.
Zinc, a very versatile chemical element
Keywords: Zinc; Metal; Galvanización; Manufactura; Perú; https://purl.org/pe-repo/ocde/ford#1.04.00